2020
DOI: 10.1016/j.echo.2020.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Nonlongitudinal Motion Components in Right Ventricular Function: Three-Dimensional Echocardiographic Study in Healthy Volunteers

Abstract: Background: Global right ventricular (RV) function is determined by the interplay of different motion components related to the myofiber architecture, and the relative importance of these components is still not thoroughly characterized. The aims of this study were to quantify the relative contributions of longitudinal, radial, and anteroposterior motion components to global RV function and to examine their determining factors in a large cohort of healthy volunteers using three-dimensional echocardiography. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 46 publications
(58 reference statements)
4
59
0
Order By: Relevance
“…For this purpose, we developed the Right VentrIcular Separate wall motIon quantificatiON (ReVISION) method a few years ago, which is a 3D echocardiography (3DE)-based solution for the quantification of the relative contribution of longitudinal, radial, and anteroposterior shortening to global RV EF (9). Since then, our technology has been applied in several clinical scenarios (10)(11)(12), and the strengths of the ReVISION method have been demonstrated in the in-depth characterization of RV mechanical pattern and the prognostication of patients even in the face of maintained RV EF (13). The ReVISION method and the associated online platform (demo version available at https://www.revisionmethod.com) are improved continuously, and recently, various new features, such as the assessment of longitudinal, circumferential, and area strains have been implemented to enable the convenient, standardized, and more comprehensive analysis of RV function using 3DE datasets.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, we developed the Right VentrIcular Separate wall motIon quantificatiON (ReVISION) method a few years ago, which is a 3D echocardiography (3DE)-based solution for the quantification of the relative contribution of longitudinal, radial, and anteroposterior shortening to global RV EF (9). Since then, our technology has been applied in several clinical scenarios (10)(11)(12), and the strengths of the ReVISION method have been demonstrated in the in-depth characterization of RV mechanical pattern and the prognostication of patients even in the face of maintained RV EF (13). The ReVISION method and the associated online platform (demo version available at https://www.revisionmethod.com) are improved continuously, and recently, various new features, such as the assessment of longitudinal, circumferential, and area strains have been implemented to enable the convenient, standardized, and more comprehensive analysis of RV function using 3DE datasets.…”
Section: Introductionmentioning
confidence: 99%
“…Although most studies have focused on longitudinal motion to generate RV ejection, our study further con rmed that RV dilation primarily occurred in the radial direction instead of the longitudinal direction. Elevated radial motion in uences systolic function via the bellows effect because the free wall of the right ventricle has a larger surface than the tricuspid annular cross-sectional area 23 . Therefore, we speculated that the improvement of ejection fraction during HE is related with not only longitudinal but also radial motion.…”
Section: Discussionmentioning
confidence: 99%
“…However, the implementation of 3DE enabled more granular understanding of RV shape and mechanics [22]. A recent study revealed that the inward motion of the free wall (radial shortening, the so-called "bellows effect") and interestingly, the anteroposterior shortening (mainly caused by the stretching of the RV free wall insertion points by the LV contraction) are of comparable significance to longitudinal shortening in healthy volunteers [23]. The bellows effect is justified by the circumferentially oriented myofibers which prevail at the subepicardial layer of the RV myocardium [22].…”
Section: Role and Relative Contribution Of Different Components Of Thmentioning
confidence: 99%